The Influence of the US Dollar-Philippine Peso Exchange Rate Fluctuations to Inflation Rates, and GDP - Anne Lorraine L. Abanto; Harvey E. Destura; Edrich Nigel A. Georsua; Hafsah D. Macaurao; Honey Niez; Ivy Paulen S. Pelonio; Lalaine O. Narsico; Peter G. Narsico (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The study aims to analyse the empirical relationship between USD/PHP exchange rate, headline inflation and real GDP growth in the Philippines from 2010 - 2024. We utilized secondary data from Bangko Sentral ng Pilipinas (BSP) and Philippine Statistics Authority (PSA) and employed descriptive statistics and bivariate linear regression models as an empirical baseline. The results show a baseline of systematic peso depreciation and stable inflation with supply-driven spikes in 2018 and 2023. The impact of the bilateral exchange rate on the variation of GDP growth is very low (R2 = 0.003) and the impact on inflation is weak and not statistically significant (R2 = 0.152). From this evidence we can say inflation and GDP are far more affected by other factors like food price, energy price and demand at home than exchange rates. Limitations include relatively small sample size and simple modelling approach. Future studies should incorporate more variables and more dynamic methods capturing the interactions between exchange rate, inflation and growth in such a complexity.